2019
DOI: 10.7717/peerj.6688
|View full text |Cite
|
Sign up to set email alerts
|

Germination characteristics among different sheepgrass (Leymus chinensis) germplasm during the seed development and after-ripening stages

Abstract: Sheepgrass (Leymus chinensis (Trin.) Tzvel) is an important forage grass in the Eurasian steppe. However, little information is available concerning its seed morphological features and germination characteristics during seed development and after-ripening among different germplasm. To clarify the appropriate seed harvest time and the effects of germplasm, seed development and after-ripening on seed germination, 20 germplasm of sheepgrass were selected. Moreover, the seed morphological and physical changes as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Afterripening has been reported in seeds that remain on dead mother plants in the field [59] and in those stored in closed containers at room temperature [59,63], in paper bags at room temperature [64,65], dry at ambient room temperature and relative humidity (RH) [66], at 30% RH at room temperature [67] and in sealed Petri dishes at 20 • C [68]. Also, afterripening is known to occur in seeds stored dry at low temperatures, for example, seeds of Hordeum vulgare L. afterripened at 8 • C [69], Berberis spp.…”
Section: Seeds That Can Afterripenmentioning
confidence: 99%
“…Afterripening has been reported in seeds that remain on dead mother plants in the field [59] and in those stored in closed containers at room temperature [59,63], in paper bags at room temperature [64,65], dry at ambient room temperature and relative humidity (RH) [66], at 30% RH at room temperature [67] and in sealed Petri dishes at 20 • C [68]. Also, afterripening is known to occur in seeds stored dry at low temperatures, for example, seeds of Hordeum vulgare L. afterripened at 8 • C [69], Berberis spp.…”
Section: Seeds That Can Afterripenmentioning
confidence: 99%
“…As such, one of the most promising dormancy-breaking techniques for T. triandra is dry storage of seed over an extended period following harvest (>6 months). Known as after-ripening, this process has been reported in seeds of a variety of species that experience a range of conditions, including un-shed seed remaining in the field on their mother plant (Baskin & Baskin, 1977), seed stored in closed containers at room temperature (Baskin & Baskin, 1977, seed stored in paper bags at room temperature (Moyo et al, 2009;Ralowicz & Mancino, 1992), seed at room temperature with varying levels of humidity (Kundu & Chaturvedi, 2019;Yang et al, 2019), and seed in sealed petri dishes at 20°C (Karimmojeni et al, 2011). The mechanism for this dormancy breakdown is not fully understood, although it is assumed that the glumes and/or lemma and palea control dormancy by containing inhibitory substances, causing mechanical restriction during germination, reducing oxygen transport to the embryo and reducing imbibition (Hagon, 1976).…”
Section: Overcoming Seed Dormancymentioning
confidence: 99%
“…Tzvel., one of the most important grassland plants in the Songnen Plain, is a perennial rhizomatous species of the Poaceae family containing high levels of proteins, mineral nutrients, and carbohydrates (Lin et al, 2016). Studies have shown that L. chinensis has a strong capacity for asexual reproduction and resistance to environmental stresses (Yang et al, 2019). The mature seedlings of L. chinensis have a strong tolerance to saltalkali stress and are the most promising gramineous plant for the rehabilitation of grassland vegetation in soils with salinizationalkalization (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%